Design of equipment suitable for measuring the natural frequency of rotating shaft - Apáti, Sándor; Hegedűs, György (Design of Machines and Structures, 2024)
In this paper, the construction and operation of a measuring bench for measur-ing the vibration state of a rotating shaft and the evaluation of the measurement results are presented. The design of the measuring bench was aimed at measuring the vibration gen-erated by the excitation effects on the shaft. The effect of the imbalance and the position of the disc on the vibration characteristics is shown in diagrams. It is also observed that at higher speeds the vibration plotted shows an irregular shape. This is due to the excitation effects on the whole structure.